An experiential investigation on internet addiction and specific disorders like depression, self-esteem and introversion among university students - Rubaiyat, Nadia; Islam, Anika; Israt, Lamiah; Kabir, Lamiya (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.